2001
DOI: 10.1021/ja003070e
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Derivatization and Fragmentation of Neutral Peptides via Ion−Molecule Reactions with Acylium Ions:  Toward Gas-Phase Edman Degradation?

Abstract: The gas-phase ion-molecule reactions of neutral alanylglycine have been examined with various mass-selected acylium ions RCO(+) (R= CH(3), CD(3), C(6)H(5), C(6)F(5) and (CH(3))( 2)N), as well as the transacylation reagent O-benzoylbenzophenone in a Fourier transform ion cyclotron resonance mass spectrometer. Reactions of the gaseous dipeptide with acylium ions trapped in the ICR cell result in the formation of energized [M + RCO](+) adduct ions that fragment to yield N-terminal b-type and C-terminal y-type pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…After absorption of this pulse, molecular species are ejected from the opposite side of the foil with relatively little energy transferred to the desorbed species [11,12]. Since LIAD is known to generate mostly neutral and intact molecules, this technique is well suited for softly producing pulses of low-polarity thermally-labile gas-phase molecules [11,13,14]. Initial studies describing the LIAD process suggested an acoustic wave mechanism for volatilization [15].…”
Section: Introductionmentioning
confidence: 99%
“…After absorption of this pulse, molecular species are ejected from the opposite side of the foil with relatively little energy transferred to the desorbed species [11,12]. Since LIAD is known to generate mostly neutral and intact molecules, this technique is well suited for softly producing pulses of low-polarity thermally-labile gas-phase molecules [11,13,14]. Initial studies describing the LIAD process suggested an acoustic wave mechanism for volatilization [15].…”
Section: Introductionmentioning
confidence: 99%
“…Other recent examples include those by Kenttämaa and coworkers who utilized ion/molecule reactions to differentiate isomeric species such as diols [20,21] and steroids [22]. In other studies, ion/molecule reactions have been utilized to develop a potential gas phase sequencing method for peptides [23], to determine enantiomeric excess [24 -26], and to explore non-covalent interactions [27]. In addition, McLuckey and coworkers have employed ion/ion proton transfer reactions to enrich specific charge states of protein ions as part of their "ion parking" methodology [28].…”
mentioning
confidence: 99%
“…systematically investigated the intrinsic reactivity of mass-selected gaseous acylium ions and have demonstrated synthetic and analytical applications of these reactions [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Gaseous acylium ions undergo the following reactions: polar [4 ϩ 2 ϩ ] cycloaddition with dienes [11,12], ketalization with diols and analogs [13,14], and transacetalization with five-and six-membered cyclic acetals [15][16][17][18][19][20] or with seven-membered acetals.…”
mentioning
confidence: 99%
“…Halogen (X) acylium ions, X™CO ϩ (F Ͼ Cl Ͼ Br), promote carbonylation of benzene [24,25] and of five-membered heterocyclics via selective functionalization of their inert C™H aromatic bonds. Gaseous acylium ions also react with neutral peptides by N-terminal derivatization followed by dissociation that produces structurally-diagnostic, modified b 1 sequence ions [26] ϩ product ions in proportions that are characteristic of the amine [27,28]. Acylium ions also react with isomeric ␣-, ␤-and ␥-hydroxyketones via structurally diagnostic cyclization reactions [29] and with ␣,␤-unsaturated carbonyl compounds by single and double [4 ϩ 2 ϩ ] Diels-Alder cycloaddition [30].…”
mentioning
confidence: 99%